Altered cerebellar‐motor loop in benign adult familial myoclonic epilepsy type 1: The structural basis of cortical tremor. Issue 12 (29th October 2022) - Wang, Ge; Song, Yanmin; Su, Jianpo; Fan, Zhipeng; Xu, Lin; Fang, Peng; Liu, Chaorong; Long, Hongyu; Hu, Chongyu; Zhou, Luo; Huang, Sha; Zhou, Pinting; et al.
Abstract: Objective: Cortical tremor/myoclonus is the hallmark feature of benign adult familial myoclonic epilepsy (BAFME), the mechanism of which remains elusive. A hypothesis is that a defective control in the preexisting cerebellar‐motor loop drives cortical tremor. Meanwhile, the basal ganglia system might also participate in BAFME. This study aimed to discover the structural basis of cortical tremor/myoclonus in BAFME. Methods: Nineteen patients with BAFME type 1 (BAFME1) and 30 matched healthy controls underwent T1‐weighted and diffusion tensor imaging scans. FreeSurfer and spatially unbiased infratentorial template (SUIT) toolboxes were utilized to assess the motor cortex and the cerebellum. Probabilistic tractography was generated for two fibers to test the hypothesis: the dentato‐thalamo‐(M1) (primary motor cortex) and globus pallidus internus (GPi)‐thalamic projections. Average fractional anisotropy (FA), axial diffusivity (AD), mean diffusivity (MD), and radial diffusivity (RD) of each tract were extracted. Results: Cerebellar atrophy and dentate nucleus alteration were observed in the patients. In addition, patients with BAFME1 exhibited reduced AD and FA in the left and right dentato‐thalamo‐M1 nondecussating fibers, respectively false discovery rate (FDR) correction q < .05. Cerebellar projections showed negative correlations with somatosensory‐evoked potential P25‐N33 amplitude and were independent of disease duration and medication. BAFME1 patients also had increased FA and decreased MD in the left GPi‐thalamic projection. Higher FA and lower RD in the right GPi‐thalamic projection were also observed (FDR q < .05). Significance: The present findings support the hypothesis that the cerebello‐thalamo‐M1 loop might be the structural basis of cortical tremor in BAFME1. The basal ganglia system also participates in BAFME1 and probably serves a regulatory role.